2000
DOI: 10.1046/j.1529-8027.2000.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in rat sciatic nerve anatomy: Implications for a rat model of neuropathic pain

Abstract: We discovered a variation of rat sciatic nerve anatomy as an incidental finding during the anatomical exploration of the nerve lesion site in a rat neuropathic pain model. To confirm the composition and distribution of rat sciatic nerve, macroscopic anatomical investigation was performed in both left and right sides in 24 adult Sprague-Dawley rats. In all rats, the L4 and L5 spinal nerves were fused tightly to form the sciatic nerve. However, the L6 spinal nerve did not fuse with this nerve completely as a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 14 publications
2
36
0
3
Order By: Relevance
“…Anatomically, the sciatic nerve in rats is formed by L4, L5, and L6 spinal roots that join to form the nerve on the lesser pelvis, in S p r a g u e -D a w l e y r a t s w a s checked that the components of sciatic nerve vary from L3 to L6, however, the major components are L4 and L5 (Asato et al, 2000). It is separated from the pudendal nerve by the superior gluteal artery.…”
Section: Macroscopicmentioning
confidence: 99%
“…Anatomically, the sciatic nerve in rats is formed by L4, L5, and L6 spinal roots that join to form the nerve on the lesser pelvis, in S p r a g u e -D a w l e y r a t s w a s checked that the components of sciatic nerve vary from L3 to L6, however, the major components are L4 and L5 (Asato et al, 2000). It is separated from the pudendal nerve by the superior gluteal artery.…”
Section: Macroscopicmentioning
confidence: 99%
“…The nerves that spread into the posterior legs originating from the plexus lumbosacrales have been studied in a variety of mammals including the dog (Miller et al, 1964;Getty, 1975), the rabbit (Barone et al, 1973;McLaughlin and Chiasson, 1987), and the rat (Green, 1968;Chiasson, 1980;Schmalbruch, 1986;Asato et al, 2000). In the porcupines (Hystrix cristata), the brachial plexus (Aydin, 2003), the nerves originating from the brachial plexus (Aydin, 2004), the morphology of circulus arteriosus cerebri (Aydin et al, 2005), and the spinal nerves that constitute the plexus lumbosacrales (Aydin et al, 2009) have been studied.…”
Section: List Of Abbreviations M = Musculus T = Thoracal L = Lumbalmentioning
confidence: 99%
“…There are many studies which which report data regarding the formation of this common root in rats. Among these, Asato et al (2000) reported that L4 and L5 always, and L6 rarely, contribute to the formation of the common root, while Vesjada and Hink (1980), Schmalbruch (1986) and Green (1968) found that L4, L5, L6, S1 and S2 are contributing nerves. In squirrels, due to the contribution of L6, L7, S1 and S2 there is a complete consistency with those findings in dogs (Miller et al, 1964;Getty, 1975;Tecirlioglu, 1983), partial consistency with reports from sheep due to the contribution of the last two lumbals and first two sacrals (Getty, 1975;Tecirlioglu, 1983;Dursun, 2000), likewise in porcupines (Aydin et al, 2009), while the findings reported here are not in agreement with the data of Getty (1975) in cattle and goats, Ebraheim (2000) in humans, Getty (1975) in cats, Cooper and Schiller (1975) in guinea pigs, McLaughlin and Chiasson (1987) in rabbits, and Asato et al (2000), Vesjada and Hink (1980), Schmalbruch (1986) and Green (1968) in rats.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies concentrating on the spinal origins of brachial and lumbosacral plexus which give off nerve branches dispersing to the fore and hind limbs on the brachial plexus: in dogs (Miller et al, 1964), in cats (Getty, 1975), the wervet monkey (Booth, 1991), Chacma baboon (Booth et al, 1997), rabbit (Aslan, 1994;Yilmaz et al, 1995), rat (Green, 1968;Chiasson, 1980) and porcupines (Aydin, 2003(Aydin, , 2004; and on the lumbosacral plexus: in dogs (Miller et al, 1964;Getty, 1975. ), rabbits (Barone et al, 1973;McLaughlin and Chiasson, 1987), rats (Green, 1968;Chiasson, 1980;Schmalbruch, 1986;Asato et al, 2000) and porcupines (Aydin, 2009;Aydin et al, 2009). In squirrels, the presence and localization of calbindin-D28k in the kidney and cerebellum (Aydin et al, 2005) and the morphology of circulus arteriosus cerebri (Aydin, 2008) were studied.…”
mentioning
confidence: 99%